Determination of Cd and Pb in Fruit Juice, Bottled Tea, Condiments and Dried Fish Samples Using ICP-MS - Magbitang, Riza A.; Bucsit, Melanie A.; Tia, Eugene S.F.; Rumbaoa, Rowena Grace; Cervas, Lowela Lou M.; Dimaya, Danica Angeline; Rodriguez, Irene B. (Science Diliman: A Journal of Pure and Applied Sciences, 2013)
Metals like cadmium (Cd) and lead (Pb) are introduced in the environment through natural processes and anthropogenic activities and may end up being present in food, where these metals may pose health risks. A method suitable for the simultaneous determination of Cd and Pb in various matrices of foodstuffs was validated and applied to different samples including fruit juice, bottled iced tea, several types of condiments, and in edible tissues of dried fish locally produced in the Philippines. Fruit juice and bottled iced tea samples were filtered prior to quantif ication of metals using inductively coupled plasma mass spectrometry (ICP-MS). Condiments and dried f ish samples were mineralized using microwave-assisted nitric acid digestion before subsequent metal detection with ICP-MS. The method was validated using cer tif ied reference materials DORM 3 and NIST 1643e, and evaluation of recovery of spiked samples.The method was linear in the concentration range 0.01 to 500μg L-1 with correlation coeff icients of 0.999 for both analytes. The estimated detection limits were 0.060 μgL-1 and 0.186 μgL-1 for Cd and Pb, respectively. The determined levels of Cd in fruit juice were in the range 0.06 ± 0.01 to 0.67 ± 0.01 μgL-1, and Pb was detected in only one sample at 0.37 ± 0.02μgL-1. For the bottled iced tea samples, Cd was detected in only one sample (0.13 ± 0.02 μgL1) while none of the samples had detectable Pb concentration. For the condiments, the determined Cd levels were in the range 0.83 ± 0.06 to 306.13 ± 2.52μgL-1, whereas the determined Pb levels were in the range 2.14 ± 0.38 to 67.45 ± 7.76μgL-1. For the dried fish samples, the Cd levels determined were in the range 2.00 ± 0.21 to 231.67 ± 5.32 μg kg-1 and that for Pb were in the range 2.38 ± 0.70 to 113.29 ± 2.25 μg kg-1. These determined levels in different foodstuffs highlight the need for routine monitoring of these contaminants. Keywords: Trace metal, fruit juices, condiments, dried f ish, microwave digestion, ICPMS